The Lausanne Theses on the Ministry and the Sacraments (1547-1548) - Bruening, Michael W. (Zwingliana, 2020)
In 1547-1548, a conflict arose within Bern’s territories over the sacraments and the power of the ministry. The Calvinist position taken by Pierre Viret and the ministers and professors in Lausanne clashed with the Zwinglian teachings dominant in Bern and supported by André Zébédée in Lausanne. At the center of the debate in spring 1548 was a collection of theses debated in Lausanne. These theses, previously believed to be lost, are published here for the first time. They reveal that the controversy in Lausanne started earlier than previously thought, that they were written over the course of several months rather than all at once, and that the author of the theses was not Viret but Lausanne theology professor Jean Ribit. Moreover, we learn for the first time the content of the ten theses condemned in Bern as contrary to the 1528 Bern Disputation. The Lausanne professors defended these theses and were supported by Simon Sulzer, Beat Gering, and Konrad Schmid, who all were expelled from Bern as a result.